Time-frequency dynamics, co-movement and causality among returns of global carbon emissions trading schemes (ETSs): A tale of four markets. (20th August 2022) - Meng, Yanli; Wang, Li; Wei, Yigang; Shi, Zhijun; Luo, Ziqian
Abstract: This study aims to explore the co-movement effect of returns among the four most representative global carbon emissions trading schemes (ETSs) and the correlations and time lag characteristics of returns in four ETSs. Specifically, this study examines the price volatility and return coherence of ETS of the European Union (EU), New Zealand, South Korea, and Shenzhen, China from 2013 to 2019 using the wavelet analysis method. Firstly, from the temporal perspective, the trading prices of the four ETSs demonstrate certain volatility characteristics, that is, more medium- and long-term (over five trading days) but less short-term fluctuations. Secondly, because of the different starting stages and maturity levels of the four major ETSs, the wavelet analysis indicates that the linkage between ETS trading rates varies across frequencies and evolves and shows dynamic characteristics from two angles of time and frequency domains. The findings also show the principle of mutual influence or linkage between global ETSs, which is helpful for the establishment of ETS and can improve the awareness of ETS risk prevention among market participants to avoid losses. Highlights: This study explores the linkage effect of returns among global major ETSs. Correlations and time lag of returns in four ETS markets were explored. Co-movement between ETSs' returns varies across frequencies and evolves over time. The four ETSs have large price fluctuations in the medium- and long-term. Shenzhen, China ETS has no significant influence on EU, New Zealand and Korea ETSs.